THE EFFECT OF ADDITION OF PROBIOTICS IN THE FEED WITH DIFFERENT DOSAGE ON THE GROWTH AND SURVIVAL RATE OF BAUNG FISH (Hemibagrus nemurus) IN AQUAPONIC SYSTEM - Fer’aini, Nadilla Eka; M Tang, Usman; Pamukas, Niken Ayu (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACKThe objective of study was to determine the effect of addition of probiotics in the feed with different dosage on the growth and survival rate of baung fish (Hemibagrus nemurus) in aquaponic system. This research was conducted from August–October 2020 at the Faculty of Fisheries and Marine Affairs, University of Riau. The container used is a bucket with a diameter of 60 cm and a height of 45 cm as many as 15 units with a stocking density of 42 fish / container.This study used a one-factor completely randomized design (CRD) method with five treatment levels and three replications.The level of treatment applied in the study was P0 = without the addition of probiotics (Control), P1 = addition of probiotics at a dose of 150 mL / kg of fish meal, P2 = addition of probiotics at a dose of 300 mL / kg of fish meal, P3 = addition of probiotics with a dose of 450 mL / gk of fish meal and P4 = addition of probiotics at a dose of 600 mL/ kg of fish meal.The best treatment was found in the addition of probiotics at a dose of 450 mL/kg of fish meal which produced protease enzyme activity 0.0929 IU/mL, absolute growth weight 7.95 grams, absolute growth length 4.80 cm, specific growth rate 3.02%, feed efficiency 67.61%, feed conversion 1.48%, and survival rate 93.65%.Keywords : Probiotics, Aquaponic, Hemibagrus nemurus